Scientific Article Writing Training for Sidoarjo Physics Senior High School Teacher Working Group: Integration of Scientific Publication in Merdeka Belajar - Deta, Utama Alan; Nurlailiyah, Alfi; Edelweiss, Mozza Pinkan; Aryani, Heny; Pratiwi, Ananda Dwi; Admoko, Setyo; Habibi, Habibi; Suprapto, Nadi; Suliyanah, Suliyanah (Universitas Lambung Mangkurat, 2025)
This Community Service activity aims to improve the skills of senior high school physics teachers in Sidoarjo in understanding the structure, writing techniques, and process of submitting scientific articles to accredited journals. The program was implemented using a Participatory Action Research (PAR) approach, which involved identifying partner needs, planning materials, conducting workshops, providing assistance with article drafting, and evaluating the program. The evaluation was conducted using a Likert-scale questionnaire, participant observation sheets, and brief interviews to measure participants' understanding and involvement. The training results showed an increase in teachers' understanding of the main components of scientific articles and an improvement in their ability to write the introduction and methods sections through guided practice sessions. The majority of participants gave “strongly agree” and “agree” ratings to the usefulness of the training, the quality of the material delivery, and the smooth implementation, with the highest percentage reaching 60%. The lowest score of 28% appeared on items related to the dynamic electricity material. Observations also showed that participants were more confident in drafting manuscripts after receiving direct assistance. Overall, this program was effective in improving teachers' basic scientific literacy and has the potential to be a strategic step in building a culture of sustainable scientific publication within the Physics teacher working group, thereby encouraging the creation of scientific works that meet the standards of national and international journals.